Programas de Exercício Físico na Terceira Idade em diferentes contextos - Ana Rita Vilela Barbosa (2017)
Aging is a worldwide reality, that induces physical, psychological and social consequences, tha can compromise the quality of life and the well-being of the older adults. This internship, integrated in the 2nd year of the Master degree in Physical Activity for the Elderly of the Faculty of Sport of the University of Porto (FADEUP), aimed to apply exercise programs in three different elderly groups in order to improve the quality of life, functionality and well-being of the participants.This report transcribes all the experiences of the professional internship, which lasted from October 2016 to June 2017. We have developed a work with3 different groups: i) muscular strength, ii) multicomponent training group, and iii) a group diagnosed with Alzheimer's Disease (AD), in a mild to moderatestage where a multicomponent program was developed. According to their caracteristics, needs and pathologies different training prescriptions weredeveloped, using FADEUP facilities. The muscle strength group, a specific muscular reinforcement workout was developed with loads adjusted to eachindividual; for the multicomponent group, the rhythmic pavilion was used and a multidisciplinary approchaiming the development of all physical capacities; forboth groups with AD, we used the volleyball pavilion and performed a multidisciplinary approch, with more incidence in cognitive, aerobic and strengthcapabilities. After Senior Fitness Test, aplied before and after trannig, we observed that the three exercise programs led to improvements in various components ofphysical fitness. This internship was indispensable for the development of my professional and personal skills, and actually I think that I'm able to respond to the demands that this area places.